RAPD ANALYSIS OF CALLUS REGENERATED AND SEED GROWN PLANTS OF MAIZE (Zea mays L.) - VASCONCELOS, MARIA JOSE VILAÇA DE; ANTUNES, MAURICIO SCHUSTERSCHITZ; BARBOSA, SOLANGE MARQUES; CARVALHO, CARLOS HENRIQUE SIQUEIRA DE (International Journal of Maize & Sorghum, 2010)
Genetic and cytogenetic changes are frequently observed in plants regenerated from tissue culture. This phenomenon, termed somaclonal variation, is undesirable in genetic transformation processes. DNA-based molecular markers have been used to characterize and evaluate genetic variability among individuals. The RAPD technique was used to evaluate somaclonal variation in maize plants derived from tissue culture from the maize inbred line L48 (derived from Suwan). Forty seven different decamer oligonucleotide primers generated 221 amplification products, 130 of them being polymorphic. Genetic divergence was calculated by the Nei´s distance based on the presence (1) or absence (0) of DNA bands in the different analyzed samples. Cluster analyses divided the samples into three distinct groups, considering an upper limit of 0.38 genetic distances. The first group included the tissue culture-derived calli, the second one the regenerated plants, and the seed-derived plants formed the last group. The results indicated that segregation was still present in the inbred line L48 after six cycles of selfing and/or that different clones of the same age accumulated different types of genetic modifications (0.05 of genetic distance). These modifications seem to be directly correlated with the potential for callus regeneration. As the age of the callus increased from 13 to 25 months, regeneration decreased about 28 times. These results indicate that RAPD technique can be used as a potent and easy-to-use tool to identify maize inbred lines less susceptible to somaclonal variation when cultured in vitro, a fundamental step in plant genetic transformation.